Two-stage surgery for a large cervical dumbbell tumour in neurofibromatosis 1: a case report - Sharifudin, Mohd Ariff; Johari, Joehaimey; Omar, Ahmad Sabri; Yusof, Abdul Halim (Malaysian Orthopaedic Association (MOA), 2011)
Spinal neurofibromas occur sporadically and typically occur in association with neurofibromatosis 1. Patients afflicted with neurofibromatosis 1 usually present with involvement of several nerve roots. This report describes the case of a 14- year-old child with a large intraspinal, but extradural tumour with paraspinal extension, dumbbell neurofibroma of the cervical region extending from the C2 to C4 vertebrae. The lesions were readily detected by MR imaging and were successfully resected in a two-stage surgery. The time interval between the first and second surgery was one month. We provide a brief review of the literature regarding various surgical approaches, emphasising the utility of anterior and posterior approaches.